Prognostic value of HLA class I expression in patients with oral squamous cell carcinoma - Koike, Kazushige; Dehari, Hironari; Shimizu, Shota; Nishiyama, Koyo; Sonoda, Tomoko; Ogi, Kazuhiro; Kobayashi, Junichi; Sasaki, Takanori; Sasaya, Takashi; Tsuchihashi, Kei; Tsukahara, Tomohide; Hasegawa, Tadashi; et al. (Cancer science, 2020)
Human leukocyte antigen (HLA) class Ⅰ molecules play a central role in anticancer immunity, but their prognostic value in oral squamous cell carcinoma (OSCC) remains unclear. We examined HLA class I expression in 2 distinct tumor compartments, namely, the tumor center and invasive front, and evaluated the association between its expression pattern and histopathological status in 137 cases with OSCC. Human leukocyte antigen class Ⅰ expression was graded semiquantitatively as high, low, and negative. At the invasive front of the tumor, HLA class I expression was high in 72 cases (52.6%), low in 44 cases (32.1%), and negative in 21 cases (15.3%). The HLA class I expression in the tumor center was high in 48 cases (35.0%), low in 58 cases (42.4%), and negative in 31 cases (22.6%). The 5‐year overall survival and disease‐specific survival rates were good in cases with high HLA class I expression at the invasive front; however, there was no significant difference in survival based on HLA class I expression in the tumor center. In addition, high HLA class I expression was correlated with high CD8+ T cell density, whereas negative HLA class I expression was correlated with low CD8+ T cell density at the invasive front. These results suggest that it is easier for CD8+ T cells to recognize presented peptides in the case of high HLA class Ⅰ expression at the tumor invasive front and could be a prognostic factor for OSCC. Human leukocyte antigen class Ⅰ expression at the tumor invasive front could be a useful prognostic factor for oral squamous cell carcinoma.